Illuminating proinflammatory myeloid cells with PET tracers targeting GPR84 - Mausam Kalita; Renesmee C. Kuo; Valentina Straniero; Samantha T. Reyes; Mallesh Pandrala; Alessia Lanzini; Sara Marsango; Desiree D’Moore; Piper Mahn; Andrew Setiadi; Mira Sundar; Spencer Mak; et al. (Proceedings of the National Academy of Sciences, 2026)
Innate immunity mediated by myeloid cells defends against infection and injury, but when chronically activated, it drives tissue damage and neurodegeneration. Molecular imaging with positron emission tomography (PET) enables noninvasive, real-time monitoring of such processes in vivo. However, most current neuroinflammation PET tracers lack specificity for activated myeloid cells. G protein–coupled receptor 84 (GPR84) is a promising biomarker that is selectively upregulated on activated microglia and macrophages. Here, we report the development and validation of two fluorine-18-labeled GPR84 tracers, [ 18 F]MGX-110S and [ 18 F]MGX-111S. Both exhibit specific binding to human GPR84-expressing cells, with [ 18 F]MGX-110S demonstrating superior affinity, selectivity, and signal-to-background ratio. [ 18 F]MGX-110S enables sensitive detection of systemic- and neuro-inflammation in LPS-treated mice and outperforms PET images obtained using a radiotracer specific for translocator protein 18 kDa in 5xFAD mice—revealing pathology-correlated activation across cortical, hippocampal, and thalamic regions. Taken together, our data indicate that [ 18 F]MGX-110S is a highly sensitive and specific tool for visualizing maladaptive myeloid cell activation; its clinical translation could enable more precise detection and staging of inflammation in addition to improved therapeutic monitoring in neurodegenerative disorders and more broadly in inflammatory diseases.